2019
DOI: 10.1016/j.ebiom.2018.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived cell-free DNA predicts allograft failure and mortality after lung transplantation

Abstract: BackgroundAllograft failure is common in lung-transplant recipients and leads to poor outcomes including early death. No reliable clinical tools exist to identify patients at high risk for allograft failure. This study tested the use of donor-derived cell-free DNA (%ddcfDNA) as a sensitive marker of early graft injury to predict impending allograft failure.MethodsThis multicenter, prospective cohort study enrolled 106 subjects who underwent lung transplantation and monitored them after transplantation for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 21 publications
5
101
0
Order By: Relevance
“…To date, the International Society for Heart and Lung Transplantation (ISHLT) Thoracic Transplant Registry has accrued data on more than 69 200 adult lung transplants ( Donor-derived cell free-DNA (dd-cfDNA) has been extensively investigated as a biomarker of "allograft injury" and has been validated for differentiation of acute cellular (ACR), antibody-mediated rejection (AMR), and quiescence after renal and cardiac transplantation [3][4][5]. After LT, Agbor-Enoh et al, while utilizing shotgun sequencing methods, described elevated dd-cfDNA levels during ACR and AMR; while the highest tertile dd-cfDNA during the initial 3-months portended a 6.6-fold increased risk for subsequent allograft failure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the International Society for Heart and Lung Transplantation (ISHLT) Thoracic Transplant Registry has accrued data on more than 69 200 adult lung transplants ( Donor-derived cell free-DNA (dd-cfDNA) has been extensively investigated as a biomarker of "allograft injury" and has been validated for differentiation of acute cellular (ACR), antibody-mediated rejection (AMR), and quiescence after renal and cardiac transplantation [3][4][5]. After LT, Agbor-Enoh et al, while utilizing shotgun sequencing methods, described elevated dd-cfDNA levels during ACR and AMR; while the highest tertile dd-cfDNA during the initial 3-months portended a 6.6-fold increased risk for subsequent allograft failure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous single-center studies after LT that used “shotgun” sequencing techniques and required genomic material from both donor and recipient have described utility of donor-derived cell-free DNA (dd-cfDNA) for detection of acute cellular rejection (ACR) and antibody-mediated allograft rejection (AMR). 1 - 3 However, these techniques are not readily applicable to routine clinical implementation for surveillance. Therefore, we assessed utility of a clinical-grade “next-generation sequencing” (NGS) dd-cfDNA assay that interrogates a panel of single-nucleotide polymorphisms with a distinct advantage that it does not require a donor genomic specimen.…”
Section: Introductionmentioning
confidence: 99%
“…cfDNA can be found in many tissues, including blood, which is thought that cfDNA is a reflection of a person’s health and disease [ 8 ]. Recently, donor-derived cell-free DNA (dd-cfDNA) has been used as a noninvasive diagnostic test; the measurement of dd-cfDNA as a fraction of the total cfDNA can detect rejection in heart, lung, liver and kidney allografts [ 9 , 10 ]. Some studies indicated that cfDNA combined with other markers could improve the diagnosis of CLAD significantly [ 11 ].…”
mentioning
confidence: 99%